FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA LUBUK PAKAM - Riskha Armayni Lubis; Bastari M; Eka Nurmala Sari (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2019)
The role of the community and taxpayers in fulfilling the obligation of payment of taxes based on tax provisions it is desirable so that taxpayer compliance in paying taxes is a strategic position in increasing tax revenues. The purpose of this research was to test and analyze the effect of taxation, taxation of socialization of knowledge, service tax, penalties and fiskus awareness taxpayer, taxpayer compliance against a private person. The research approach used in this study is the associative approach. The population in this research is the whole personal person taxpayer (WPOP) which has as much as much as the person 13,731 NPWP and samples retrieved 100 respondents. Dianlisis data using multiple regression test. The results showed that knowledge of taxation taxpayer compliance have an effect on people, socializing taxation positive taxpayer compliance have an effect on people, the Ministry of taxation impact fiskus private person positive taxpayer compliance, tax compliance to sanctions positive taxpayer private person, taxpayer awareness of compliance to mandatory tax, taxation, taxation of socialization of knowledge service fiskus, penalties and taxation positive taxpayer awareness of compliance to mandatory tax people privately.